GAMBARAN TINGKAT PENGETAHUAN PENGENDARA SEPEDA MOTOR TENTANG PENYAKIT INFEKSI SALURAN PERNAFASAN AKUT DI WILAYAH PASAR PANCASILA TASIKMALAYA - Riyana, Asep; Rahman, Arip; A.S Hidayat, Asep (Fakultas Ilmu Kesehatan Universitas Siliwangi, 2023)
Motorbike riders, especially those who work as motorbike taxi drivers, are very at risk of being negatively impacted by air pollution which will affect their health status, such as acute respiratory infections. Motorcyclist knowledge about ISPA is one of the main assets in improving health status and minimizing the incidence of ISPA. ISPA is a respiratory tract infection that lasts up to 14 days and can be transmitted through saliva, blood, sneezing or air. The aim of this research is to determine the level of knowledge of motorcyclists about ISPA in the Pancasila Market Area, Tasikmalaya City. The design of this research is descriptive research, the population in the research is motorbike taxis in the Pancasila Market Area as many as 112 people, the sample studied was 24 people using purposive sampling techniques. Data analysis used frequency distribution. The results of the research show that the knowledge of motorcyclists about ISPA in the Pancasila Market Area is mostly in the Fair category (54%), regarding the meaning of ISPA is equally large, namely in the good (50%) and Fair (50%) categories, regarding signs and symptoms ISPA is mostly in the Poor category (46%), about the causes of ISPA mostly in the Fair category (46%), about factors influencing ISPA mostly in the Poor category (42%), about preventing ISPA mostly in the Good category (71 %). It is hoped that health workers will provide education, especially about ISPA.